2020
DOI: 10.3389/fchem.2020.00193
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Aggregation-Induced Delayed Fluorescence Luminogens for Solution-Processed OLEDs With Small Efficiency Roll-Off

Abstract: Purely organic small molecules with thermally-activated delayed fluorescence have a high potential for application in organic light-emitting diodes (OLEDs), but overcoming severe efficiency roll-off at high voltages still remains challenging. In this work, we design and synthesize two new emitters consisting of electron-withdrawing benzoyl and electron-donating phenoxazine and 9,9-dihexylfluorene. Their electronic structures, thermal stability, electrochemical behaviors, photoluminescence property, and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, upon formation of rigid assemblies such relaxation processes are highly restricted thereby prolonging the life time of the excited states of the clusters and making them available for ISC and reverse ISC. 36…”
Section: Resultsmentioning
confidence: 99%
“…However, upon formation of rigid assemblies such relaxation processes are highly restricted thereby prolonging the life time of the excited states of the clusters and making them available for ISC and reverse ISC. 36…”
Section: Resultsmentioning
confidence: 99%
“…While there has been vast development of new TADF emitters and our understanding of the fundamental processes of rISC and the spin states has developed, it is now time to look towards understanding these processes in non-ideal situations using the techniques and framework discussed above. This framework will facilitate the development and understanding of functional materials that are sensitive to mechanical and thermal energy while opening up pathways to AIE-based, non-doped OLEDs (Furue et al, 2016;Liu et al, 2018a;Cai et al, 2020;Yang et al, 2020). It will also help unify the study of intramolecular TADF emitters with the studies of polymorphism (Chung and Diao, 2016;Bernstein, 2020;Levesque et al, 2020) exciplexes (Kim et al, 2016;Sarma and Wong, 2018;Tang et al, 2020) and hostguest interactions (Matsunaga and Yang, 2015;Feng et al, 2017;Ono et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…8 c To better understand this phenomenon, several synthetic modifications and theoretical calculations were undertaken; the results revealed that the restriction of intramolecular motions, which led to rotation, vibration, and stretching, played a key role in the AIE phenomenon. Several synthetic modifications on organic fluorophores have been developed for AIE materials including siloles, 9 triphenylamine (TPA), 10 cyanostilbenes, 11 tetraphenylethenes, 12 a – d naphthalenediimide 12 e , f and anthracene 13 derivatives, diphenyldibenzofulvenes, 14 BODIPYs, 15 diketopyrrolopyrrole, 16 and fluorene derivatives, 17,18 The enhanced emission of all the AIEgens in their aggregate and solid forms is due to the nonplanar aromatic backbone that restricts the formation of π–π stacking. 5 On the other hand, supramolecular self-assembly of π-conjugated organic fluorescent molecules exhibits the AIE property in the aggregate state.…”
Section: Introductionmentioning
confidence: 99%